PSYCHOLOGICAL FITNESS AS AN AREA OF DEVELOPMENT OF PSYCHOLOGICAL PRACTICE - Dekhkanboeva Z. D. (Web of Journals Publishing, 2024)
The article considers psychological fitness as a direction for the development of psychological practice, and draws conclusions and methods for improvement.
Keywords: fitness practices, involvement, motivational factors, corporeality, satisfaction with one's own appearance.